Causes de non intégration de la langue française aux élèves de degré moyen de quelques écoles de Mombesa(RDC) - ALALY LIKUNDE, Simon- pierre; BONGENDE, Léa MBASA (IJRDO- Journal of Educational Research, 2017)
This work concerns causes of no integration of French language to pupils of middle degree in some schools of collectivity sector of Mombesa. The concern articulated around the following question: what causes are bases of no integration of French language to pupils of middle degree in some schools of collectivity sector of Mombesa? The hypothesis is the following one: the causes of no integration of French language to pupils of the middle degree in secondary schools of collectivity sector of Mombesa would be: Under qualification of teachers, the lack of documentations thorough, The negligence of courses by pupils, the no application of discipline rules by the school. The objective of the study is to determine causes whose are bases of no integration of French language to pupils of middle degree in some schools of collectivity sector of Mombesa